Central and Decentral Aspects of Land Use: Optimizing Public Finance and Payments for Nature in Space by Control Theory - Ernst-August Nuppenau (Operations Research Forum, 2022)
Payments for eco-system services and nature (words are used synonymously) cannot be treated independently from spatial outlays. We adopt a modified "von Thünen" framework and ask for optimal land allocation in space in case of land rent change and regional preference. Yet, our approach is not circular; rather, we see provision of nature along transport routes (stretches, i.e. within a segment or wedge of circle) and ask whether nature (conservation) should be closer to cities or in the periphery; i.e. in terms of priorities, which are planning variables, nature is reckoned as integrated in farming instead of being a segregated entity. For the conflict of amenities from nature (usually wished closer to cities because of lesser transport costs for citizens) vs. provision at the periphery (because of lower opportunity costs), we develop a model which optionally foresees both nature along cities and in peripheral areas. Hereby, we work on the explicit question of land distribution between the two options in space. Our planning approach optimizes nature shares along a gradient from urban to peripheral areas. Further, we include land price dynamics, in general already very pronounced today in intensively used landscapes around cities, and reference to the situation that land prices close to cities are usually quite a bit higher than in periphery. This requests larger payments, inflicted on overall efficacy of programs. As nature provision conflicts with food provision and provate land use, models should also comprise food needs of cities. Yet, we reckon spatial opportunity costs and costs are minimized. Benefits in space for citizens are also spatially distributed. We suggest using control theory in order to attain a comprehensive analysis for and answer to regional priority setting. Archetypally, an integrated vs. a segregated nature provision concept is pursued; nature becomes relatively arranged in a mixed landscape, and farmers receive payments differently.
Keywords: 510; Spatial modelling; Nature provision; Dynamic optimization; Financial flows; Environmental and eco-system service management